Comparative secretome analysis of obese perivascular adipose tissue reveals impaired adipose-neuronal crosstalk. (10th June 2022) - Duregotti, E; Reumiller, C; Mayr, U; Hasman, M; Schmidt, L; Burnap, S A; Theofilatos, K; Barallobre-Barreiro, J; Viviano, A; Jahangiri, M; Mayr, M
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): BHF Programme Grant (RG/16/14/32397) VASCage-Research Center on Vascular Ageing and Stroke (No. 868624) Background: While canonical adipose tissue (AT) depots have been extensively characterised in health and disease, comparatively little is known about the pathological changes affecting the perivascular AT's (PVAT) physiology during obesity. Purpose: The aim of this study was to study the impact of obesity on the secretory activity of the murine PVAT. Methods: We exploited proteomics to profile the secretome of peri-aortic and canonical AT depots in wild-type (wt) and obese (ob/ob) mice. In parallel, fat tissues were processed for biochemical and histological analysis and mechanistical experiments were performed in vitro on primary neuronal cultures. Results: Proteomics on ATs conditioned media from wt mice revealed that each fat depot displays a unique secretory profile. The enrichment of neuronal cell-adhesion molecules detected in PVAT secretomes reflected a higher content of intra-parenchymal sympathetic projections compared to non-perivascular ATs. A significant decrease of the same neuronal proteins in PVAT conditioned media from ob/ob mice was found to be associated with a substantial reduction of the perivascular sympathetic innervation. Intriguingly, a similar decrease of sympathetic markers was detected in the epicardial AT from obese patients. Mechanistically, the conditioned media from ob/ob AT explants was found to exert a deleterious effect on the axons of primary sympathetic neurons in vitro, indicating that this neuropathy is due to local alterations of the PVAT secretome that detrimentally impact on the embedded sympathetic neurites. Among proteins significantly down-regulated in the secretomes of ob/ob PVAT samples, neuronal growth regulator 1 (Negr1) was found to promote axonal elongation and branching on sympathetic neurons in vitro. Administration of recombinant Negr1 also partially restored the neurotrophic effect of ob/ob AT secretomes on sympathetic axons both in vitro and in vivo. Conclusions: Obesity-related alterations in the secretome of PVAT severely affect the homeostasis of the perivascular environment, leading to a loss of perivascular sympathetic innervation. A novel neurotrophic role is unveiled for Negr1, whose locus has been associated with human obesity.